2012
DOI: 10.1038/eye.2011.365
|View full text |Cite
|
Sign up to set email alerts
|

A new, pachymetry-based approach for diagnostic cutoffs for normal, suspect and keratoconic cornea

Abstract: Purpose To analyze whether an association exists between keratometric and pachymetric changes in the cornea, and whether it can be used to create pachymetric cutoff criteria secondary to keratometric criteria. Methods In this cross-sectional study, 1000 candidates presenting to the refractive surgery services of a tertiary care hospital underwent bilateral Orbscan IIz (Bausch and Lomb) assessment along with other ophthalmic evaluation.Results Stepwise regression analysis-based models showed that simulated kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Although pachymetry based diagnostic algorithms are still being investigated, corneal pachymetry was not included in the formula of indices introduced by Rabinowitz-McDonnell [5,6,8,[18][19][20]. In the present study, ROC analysis of each Scheimpflug parameter revealed that both Kmax and TP had high diagnostic ability in discriminating keratoconic eyes from normals (with sensitivity-specificity values of 92.9-92.4% and 89.6-93.3%, respectively).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although pachymetry based diagnostic algorithms are still being investigated, corneal pachymetry was not included in the formula of indices introduced by Rabinowitz-McDonnell [5,6,8,[18][19][20]. In the present study, ROC analysis of each Scheimpflug parameter revealed that both Kmax and TP had high diagnostic ability in discriminating keratoconic eyes from normals (with sensitivity-specificity values of 92.9-92.4% and 89.6-93.3%, respectively).…”
Section: Discussionmentioning
confidence: 72%
“…Hence, many researchers developed valuable indices and maps [5][6][7][8][9][18][19][20][21][22]. Rabinowitz and McDonnell [5] introduced the central K and dioptric difference between inferior and superior area (I-S).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, recent attempts have shown the possibility to grade the keratoconus also on the pachymetric and corneal wavefront changes. [2][3][4][5][6][7] Authors have included a combination of these factors such as topography & pachymetry, topography & corneal aberrations/biomechanics to create composite grading scales. 4,[6][7][8][9] However, the ideal result would be to create a combined, multifactorial grading scale.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Authors have included a combination of these factors such as topography & pachymetry, topography & corneal aberrations/biomechanics to create composite grading scales. 4,[6][7][8][9] However, the ideal result would be to create a combined, multifactorial grading scale. This seems biologically plausible because the changes seen in progressive keratoconus, such as increase in the corneal steepness, worsening of the wavefront profile and decreased corneal thickness are the manifestations of a same disease process.…”
Section: Introductionmentioning
confidence: 99%
“…They reached a sensitivity and specificity of 82.00 and 80.00% respectively. In addition, Prakash et al 18 have proposed cut-off values of pachymetry in keratoconic patients using Orbscan IIz system. Their results suggest that a cornea with minimal pachymetry <461 µm or a difference between the minimum pachymetry and corneal central thickness greater than 27 µm has 97.50% risk of being suspected keratoconus or clinical keratoconus, and therefore, only 2.50% are likely to be normal.…”
Section: Discussionmentioning
confidence: 99%